Determinants of Firm Growth through Sales as an Intervening Variable: A Comprehensive Multi-Variable Model in the Garment Industry - Dedy Triyono; Aminullah Assagaf; Liosten Rianna Roosida Ully Tampubolon (Business and Applied Management Journal, 2026)
The garment industry contributes significantly to Indonesia’s economic development and employment generation. However, increasing competition, the emergence of substitute products, changing consumer lifestyles, and rapid digital transformation present major challenges to firm growth. Previous studies have generally examined these factors separately, resulting in limited understanding of their combined influence on business performance. This study investigates the determinants of firm growth by integrating competitors, substitute products, product innovation, digital marketing, social media, lifestyle, and consumer preferences into a comprehensive model, with sales serving as an intervening variable. A quantitative explanatory approach was employed using survey data from 377 garment business owners and managers in East Java, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that competitors, lifestyle, and consumer preferences positively and significantly affect both sales and firm growth. Substitute products significantly influence firm growth but have no significant effect on sales, whereas digital marketing positively affects sales without directly influencing firm growth. Product innovation and social media show no significant effects on either sales or firm growth. Sales significantly contribute to firm growth but do not mediate the relationships between the examined determinants and firm growth. These findings provide an integrated perspective on firm growth and offer practical implications for garment businesses in developing adaptive and competitive growth strategies.